Onset of deglacial warming in West Antarctica driven by local orbital forcing - Fudge, T.J.; Steig, Eric J.; Markle, Bradley R.; Schoenemann, Spruce W.; Ding, Qinghua; Taylor, Kendrick C.; McConnell, Joseph R.; Brook, Edward J.; Sowers, Todd; White, James W.C.; Alley, Richard B.; Cheng, Hai; et al. (Nature Publishing Group, 2013)
The cause of warming in the Southern Hemisphere during the most recent deglaciation remains a matter of debate. Hypotheses for a Northern Hemisphere trigger, through oceanic redistributions of heat, are based in part on the abrupt onset of warming seen in East Antarctic ice cores and dated to 18,000 years ago, which is several thousand years after high-latitude Northern Hemisphere summer insolation intensity began increasing from its minimum, approximately 24,000 years ago. An alternative explanation is that local solar insolation changes cause the Southern Hemisphere to warm independently. Here we present results from a new, annually resolved ice-core record from West Antarctica that reconciles these two views. The records show that 18,000 years ago snow accumulation in West Antarctica began increasing, coincident with increasing carbon dioxide concentrations, warming in East Antarctica and cooling in the Northern Hemisphere associated with an abrupt decrease in Atlantic meridional overturning circulation. However, significant warming in West Antarctica began at least 2,000 years earlier. Circum-Antarctic sea-ice decline, driven by increasing local insolation, is the likely cause of this warming. The marine-influenced West Antarctic records suggest a more active role for the Southern Ocean in the onset of deglaciation than is inferred from ice cores in the East Antarctic interior, which are largely isolated from sea-ice changes.